Beragam Peran Media Sosial dalam Dunia Politik di Indonesia - Munzir, Atika Aisyarahmi (JPPUMA Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2019)
The presence of the internet as a communication and information technology that continues to innovate can give birth to a variety of social media that can be used by an individual for various purposes. Aside from being a means of communicating in cyberspace, social media classified as new media can be used as an effort to present one's self-image including politicians. Now social media can not be separated from the daily life of an individual. Not only as a social need, but the use of social media was able to give influence in the political world. Fast, inexpensive, and effective making social media the most important communication tool in politics. This article aims to discuss the various roles of social media in the political world in Indonesia. The method used is quantitative by identifying the text. The author will use the framing analysis method by taking three research results that explain the various roles of social media in the political world. The results of article writing explain that the role of social media in the political world in Indonesia is as a media campaign, the development of political literacy, and increased voter participation.